Nightjohn - Paulsen, Gary. (New York : Delacorte Press, 1993)
Twelve-year-old Sarny's brutal life as a slave becomes even more dangerous when a newly arrived slave offers to teach her how to read.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
4.2
Young Adult
Keywords: Reading -- Fiction; Slavery -- Fiction; Reading -- Fiction; Slavery -- Fiction; Historical fiction